Insight into the effect of biaxial compression strain on adsorption structure of bituminous coal matrix as well as gas diffusion and permeability properties by macromolecule simulation. (15th April 2023) - Zhang, Qing; Zhu, Hongqing; Kang, Rongxue; Zhang, Lei; Fang, Shuhao; Hu, Lintao; Qu, Baolin; Liao, Qi
Highlights: Rationality of macromolecular bituminous coal model was verified. Effect of strain on adsorption concentration of CH4 /CO2 /N2 was analyzed. Effects of strain on swelling parameters, mechanical parameters and cohesive energy density were elucidated. Effects of strain on diffusion properties of gases were discussed. Compression strain has dual effect of promoting and inhibiting coal matrix permeability. Abstract: The concentrated stress induced by mining activities leads to deformation of the coal, especially the coal matrix, which affects the production of coalbed methane (CBM). Therefore, grand canonical Monte Carlo and molecular dynamics methods were used to study the effect of biaxial compression strain on the adsorption structure of the bituminous coal matrix as well as the CH4 /CO2 /N2 diffusion and permeability properties based on the constructed macromolecular coal model. The results show that the dual-mode equation fits the gas adsorption isotherm and the order of influence of adsorption concentration on the model structure is N2  > CO2  > CH4 . For the diffusion models, the orders of swelling rate and specific volume are CH4  > N2  > CO2, while those of the fractional free volume and pore volume are opposite. Compression (negative) strain (0.00 ∼ −0.20) reduces the bulk modulus but has a negligible effect on the shear modulus and wave velocity. Also the Poisson's ratio of the CH4 diffusion model is smaller compared to the CO2 /N2 diffusion model. The cohesive energy density ( CED ) order is CO2  > N2  > CH4 and its van der Waals component accounts for the major part. The mean square displacement distribution of gases successively increases in the power function and linearity with time. The self-diffusion coefficient of CH4 is larger than that of CO2 /N2, which is greatly affected by strain. The (negative) interaction energy order between gas and coal matrix is CH4  > N2  > CO2, and the order of intermolecular interaction distance of gases is N2  > CO2  > CH4 . Most importantly, the solubility order of gases is CO2  > CH4  > N2, and the strain has the dual effect of promoting and inhibiting the permeability of the coal matrix. The research results provide molecular-level insights into CBM recoveries in coal reservoirs with different strain degrees, with some technical value and theoretical importance.